Corruption abuse of humanitarian and free aid in the context of armed conflicts: a comparative legal study (Law and Safety, 2022)
The article is devoted to the analysis of an extremely important topic under martial law, which is the characteristics of certain corrupt practices in relation to free and humanitarian aid in foreign countries and Ukraine, with the aim of finding optimal ways to combat corruption in the sphere of rational and effective use of free and humanitarian aid during armed conflicts.It has been noted that with the beginning of the first states existence, the initial forms of corruption abuse by officials, priests and other persons endowed with power also appeared. The first attempts to combat corruption date back to the times of Babylon and Ancient Egypt. However, corruption is a very specific phenomenon that skillfully adapts to any life circumstances, changes in political regimes, forms of government, etc.A complex of scientific research methods has been used, namely: comparative and legal, systemic and structural, logical, analysis and synthesis, generalization and prognostic. It has been substantiated that combating corruption in relation to humanitarian aid is an extremely important task in the context of military operations, since corruption: 1) limits the amount of aid that reaches people in need; 2) is one of the main factors preventing better and more direct funding of humanitarian organizations; 3) undermines support for aid in donor countries and negatively affects the international image of the state.Based on the analysis of the foreign states that are in armed conflicts and international donor organizations experience, it has been proposed to implement separate practical anti-corruption measures to ensure the leveling of corruption risks regarding the rational use of humanitarian and charitable assistance.